Impact of the MSU-Sulu College of Agriculture's Patikul Extension Program on Local Students - . Sammah, Merhama M.; Marajuli, Fatima Sheirene M.; Sammah, Ronnie H.; Ahajani, Nedzfa A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study examined the positive impacts of the MSU-Sulu Col-lege of Agriculture's Patikul Extension Program on students from Patikul Municipality. It focused on three key areas: socio-cultural, economic, and environmental aspects. Data was collected through a structured survey, which included two sections: one for demo-graphic information and another for assessing program impacts. The responses were analyzed using weighted means, inferential statistics, and one-way ANOVA to identify significant differences across respondent profiles.Key findings revealed that most respondents were female, aged 25 or older, and first-year students. In terms of impact, the socio-cultural aspect had the highest rating (4.58, "Strongly Agree"), fol-lowed by the environmental (4.46, "Agree") and economic aspects (4.42, "Agree"). Significant differences were found in responses based on respondent profiles across all three impact areas.The study recommends enhancing the program by investing in faculty development, improving facilities and laboratories, and conducting further research on the program's long-term effects on stakeholders.